Monitoring of PCBs at facilities related with PCB-containing products and wastes in South Korea - Jin, Guang-Zhu; Fang, Ming-Liang; Kang, Jung-Ho; Park, Hyokeun; Lee, Sang-Hyup; Chang, Yoon-Seok (ELSEVIER, 2011)
Polychlorinated biphenyl (PCB) contents were analyzed in samples collected from facilities related to PCB-containing products or wastes in South Korea. Average concentrations of the atmospheric Sigma(209) PCBs were 7420 (37.0-104,048) pg m(-3) and 16.8 (ND-34.2) fg WHO-TEQ m(-3) in indoor air samples; and 1670 (106-13,382) pg m(-3) and 5.64 (ND-36.0) fg WHO-TEQ m(-3) in outdoor air samples. The highest levels were observed in indoor air samples from disposal facilities (7336-104,048 pg m(-3)), followed by production (330-25,057 pg m(-3)), recycling, and storage facilities, indicating that PCB emissions from PCB-containing products and wastes remains very high and the facilities related with those may be an important source to atmospheric PCBs. Principal component analysis of PCB profiles showed that the homologue patterns of PCBs in outdoor and indoor air samples collected from the facilities were similar to those of boundary air samples and PCB commercial products, e.g. Aroclor 1016, 1221, 1232 and 1242. Evaluation of the PCB mass balance in a facility, dismantling and solvent-washing PCB-contaminated transformers, showed that of the total PCBs treated in this facility, approximately 0.0022% was emitted to the atmosphere, and most was transferred to waste oil for disposal by incineration or chemical methods. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: POLYCHLORINATED-BIPHENYLS PCBS; HISTORICAL EMISSION INVENTORY; SOURCE IDENTIFICATION; ATMOSPHERIC PCBS; PCDD/FS; AIR; FORMULATIONS; CONGENERS; URBAN; AREA